The Fiscal State in Africa: Evidence from a century of growth - Thilo N. Albers; Morten Jerven; Marvin Suesse (African Economic History Network (AEHN), 2020)
Why do large differences in fiscal capacity exist between states in the Global South? We construct a comprehensive new dataset of tax and revenue collection for 46 African polities from 1900 to 2015. Descriptive analyses show that many polities in Africa have been characterized by strong growth in real tax collection. As a next step, we employ these data to test theories of fiscal capacity in a long-run panel setting, using fixed-effects and causal estimation techniques. The results show democratic institutions and interstate warfare can increase fiscal capacity, while government turnover reduces it. However, these factors are conditional on the availability of debt financing and external aid, which by themselves reduce incentives to invest in fiscal capacity. Leveraging new data on exogenous movements in commodity prices, we show that resource income does not generally lead to lower capacity. These insights add important nuance to established theories of state-building.
Keywords: E62; N17; N47; 330; Africa; Fiscal Capacity; Fiscal State; Taxation